Wonderland Earth in the Anthropocene Epoch (University of Mary Washington) - Rolston, Holmes, 1932-2025, speaker; Mikhalevsky, Nina, speaker; Matzke, Jason, speaker; Colorado State University, producer (Colorado State University. Libraries, 2018)
This lecture by Holmes Rolston III was the keynote lecture at a conference, Wild Places, Natural Spaces, the fourteenth annual conference of the International Association for the Study of Environment, Space, and Place, at the University of Mary Washington, Fredericksburg, Virginia, on April 27-29, 2018. Rolston asks about (1) Earth as a wonderland planet, about (2) humans as the wonder of wonders on Earth. He continues (3) wondering about Anthropocene humans and their efforts to build a (4) managed planet bringing about the end of nature. He worries that this is (5) Anthropocene arrogance, and recommends, instead that these (6) wonderful humans should consider themselves incarnate on and caring for their wonderland Earth.
Videotaped at the University of Mary Washington and produced at Colorado State University.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: natural history; evolution; human nature; mind; pride; arrogance; respect for nature; value in nature; Earth; future of Earth; Anthropocene Epoch; environmental ethics